The Influence of Subject Teacher Deliberation (Mgmp), Teacher Resilience, and Academic Supervision on Cultural Arts Learning Quality in Gresik Regency Junior High Schools - Elly Nurdjanah; Amrozi Khamidi; Yatim Riyanto; Kaniati Amalia (Dinasti Publisher, 2025)
His study aims to analyze the influence of subject teacher forums (MGMP), teacher resilience, and academic supervision on the quality of learning in public junior high schools in Gresik Regency. The research employed a quantitative approach with a survey method, involving 30 arts and culture teachers as respondents. Data were collected using validated and reliable questionnaires and analyzed through multiple regression analysis. The findings reveal that MGMP, teacher resilience, and academic supervision each have a positive and significant effect on the quality of learning. MGMP contributes by enhancing pedagogical competence and encouraging collaborative practices among teachers. Teacher resilience supports the ability to adapt and remain committed under various educational challenges. Academic supervision functions as a professional development tool, providing reflective feedback to improve teaching practices. Simultaneously, these three factors influence learning quality by 92.2%, emphasizing the importance of an integrated approach in improving educational outcomes. The study concludes that strengthening teacher professionalism, emotional endurance, and supervisory systems is crucial in achieving sustainable improvements in the quality of education at the junior secondary level.